Exploring the motivations behind food self-provisioning in the Czech Republic - Tereza Pilařová; Steffen Muench; Miroslava Bavorova; Jan Huml (Agricultural Economics (AGRICECON), 2023)
Gardening and food self-provisioning motivations are changing with the country's economic development. While food security is often the main driver for self-provisioning in low-income countries, more diverse motivations exist in high-income countries. This study investigates the motivations for self-provisioning in the Czech Republic and the role of the family composition on the rate of self-provisioning to explore its social benefits. A two-step analysis was employed using data collected from 1 214 respondents. First, an exploratory descriptive statistical analysis was conducted to gain insights into the motivation of different households participating in self-provisioning. Second, binary probit models were used to investigate the characteristics influencing the main motives for self-provisioning. The results of the models revealed that the educational level, income per capita, family structure and area of residence influence the motives for self-provisioning.